Comparison of Limited and Aggressive Open Lumbar Discectomy in Terms of Clinical Recurrence Complications, Discitis, Osteomyelitis and Postoperative Lumbar Pain - Nazemi Rafie, Ali; Lotfipour, Alireza; Kamali, Alireza; Mohammadi, Alireza; Dalvandi, Mohsen (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Low back pain is still one of the major public health problems. According to studies done today, back pain after a cold is the second cause of job absence. 70 to 80% of people in the world suffer from low back pain, which eventually leads to consultation with a physician and other health care providers for evaluation and treatment. Each year, governments spend heavily on diagnosing, treating, and coping with back pain disabilities. The aim of this study was to evaluate and compare two methods, limited and aggressive open lumbar discectomy, in terms of clinical recurrence complications, discitis, osteomyelitis, and postoperative lumbar pain. Materials and methods: In this study, sampling was done from patients referred to the neurosurgery ward of the hospital from 2016 to 2018. The study population included patients with lumbar disc herniation pain requiring surgical intervention and entered the study with inclusion criteria. Two surgical methods were used to perform the discectomy in patients. For the purpose of this study, the sample size with 80 power study and 95% significance level of the calculated volume is equal to 70 samples. Finally, the data were entered into SPSS software to make sample size and thus statistical analysis with the help of this software. Results: The mean age of the first group was 35.57 years, and in the second group it was 9.34 years. The incidence of discitis with osteomyelitis was one case for the first group (2.5%) and two cases for the second group (5%). The rate of recurrence of the disc was evaluated: three cases for the first group (7.5%) and two cases for the second group (5%). The mean preoperative pain score was 7.95 for the first group, and 7.6 for the second group was obtained from 10. There was no significant difference between the two groups in the rate of disc recurrence during the six months after surgery (P-value = 0.18). Associated risk was also assessed for the incidence of discitis and osteomyelitis in the two groups, with no significant difference (P-value = 0.12). The mean pain reduction score one day after surgery was 5.1 for the first group and 4.625 for the second group, with no significant difference (P-value = 0.29). Conclusion: According to the results of this study on the treatment of lumbar disc herniation with high evidence, it can be concluded that sequestrectomy surgery, due to shorter operation time, less manipulation of natural regional elements, and lack of obvious difference in incidence of disc recurrence, is preferable to the aggressive method. Of course, some searches showed an increased recurrence rate in these patients, butsive meta-analyses reject this finding.